Literature, Memory and Identity. A Theoretical View. - Maldonado Alemán, Manuel (Revista de Filología Alemana, 2011)
The close relationship between memory, in terms of the act of remembering, and identity, in terms of the set of features and circumstances defining and distinguishing a person or social 1 group, is a recurring theme in contemporary literature, not only in Spain but also in other countries that have undergone profound social and political change in the recent past. Such is the case of Germany. Today’s narratives especially tend to express aesthetically the process of remembering and forgetting undergone by a series of individuals or groups, in order to recreate imagined identities through their own particular view of the past. Making use of specific formal processes, this narrative gives shape to a range of concepts and forms of constructing memory and identity in different ways, projecting, sometimes superficially, other times in surprising detail, a set of highly symbolically loaded identitarian models that can have a decisive influence on the modes adopted in contemporary society by individual and group processes of evoking the past and constructing identities. This article takes a theoretical view of the concepts of memory and identity and of the specific function fulfilled by literature in their expression.
Keywords: Memory and Literature; Memory and Identity; Post-Dictatorial Writing; Literary